La nature du progrès technique et la substitution des facteurs dans les pays en voie de développement - Hawrylyshyn, Oli (L'Actualité économique, 1977)
AbstractThe first part of the paper presents a new typology of direction of technological progress which is more suited to the problem of employment in developing countries, and factor substitution effects. An alternative to elasticity of substitution is proposed as providing more insights into the employment problems, namely the "range of substitution". The main conclusions here are that labour-saving technological progress as usually defined does not necessarily mean a reduced scope for substitution, contrary to the popular view of the technological determinist, but that nevertheless the most desirable direction of progress is in the neighborhood of the labour-intensive ridge line. The second part of the paper then considers how progress can be so directed. First, technological progress is narrowly defined not as a shift of the isoquant but as a movement of a particular process-point on the isoquant, reflecting the practical nature of R&D.Concluding that new technology is the result of efforts and resources denoted to a process, the paper infers from that the following policy implication: to improve employment opportunities, R&D resources must be oriented to labour-intensive processes, either by incentives or more explicitly. As a cautionary note, it is suggested factor prices do nevertheless matter, and technical efficiency is still an important criterion.